Phytochemical study on Ochrosia Oppositifolia and Kopsia Singapurencis (Apocynaceae) - Tan Siow Ping (Tanjong Malim, 2012)
Phytochemical study on Ochrosia Oppositifolia and Kopsia Singapurencis (Apocynaceae) by Tan Siow Ping